Mixing a musical : Broadway theatrical sound techniques - Slaton, Shannon (Routledge, 2019)
Mixing a Musical: Broadway Theatrical Sound Techniques, Second Edition pulls the curtain back on one of the least understood careers in live theatre: the role and responsibilities of the sound technician.